Outcomes of extended radical resections for locally advanced and recurrent pelvic malignancy involving the aortoiliac axis. (11th February 2020) - Peacock, O.; Smith, N.; Waters, P. S.; Cheung, F.; McCormick, J. J.; Warrier, S. K.; Wagner, T.; Heriot, A. G.
Abstract: Aim: Currently, there is no clear consensus on the role of extended pelvic resections for locally advanced or recurrent disease involving major vascular structures. The aims of this study were to report the outcomes of consecutive patients undergoing extended resections for pelvic malignancy involving the aortoiliac axis. Methods: Prospective data were collected on patients having extended radical resections for locally advanced or recurrent pelvic malignancies, with aortoiliac axis involvement, requiring en bloc vascular resection and reconstruction, at a single institution between 2014 and 2018. Results: Eleven patients were included (median age 60 years; range 31–69 years; seven women). The majority required resection of both arterial and venous systems ( n = 8), and the technique for vascular reconstruction was either interposition grafts or femoral–femoral crossover grafts. The median operative time was 510 min (range 330–960 min). Clear resection margins (R0) were achieved in nine patients. The median length of stay was 25 days (range 7–83 days). Seven patients did not suffer an early complication. There was one serious complication (Clavien–Dindo ≥ 3), an arterial graft occlusion secondary to thrombus in the immediate postoperative period, requiring a return to theatre and thrombectomy. The median length of follow‐up in this study was 22 months (range 4–58 months). Conclusion: This series demonstrates that en bloc major vascular resection and reconstruction can be performed safely and can achieve clear resection margins in selected patients with locally advanced or recurrent pelvic malignancy at specialist surgery centres.